Fragments of SLIT3 inhibit cellular migration - Schubert, Thomas; Denk, Alexandra E.; Ruedel, Anke; Kaufmann, Simone; Hustert, Elisabeth; Bastone, Patrizia; Bosserhoff, Anja K. (International Journal of Molecular Medicine, 2012)
The repellent factor family of Slit molecules has been described as having a repulsive function in the developing nervous system on growing axons expressing the Roundabout (Robo) receptors. Recent studies determined the effects of Slit molecules on the migratory and invasive potential of several types of tumor cells but also on synovial fibroblasts (SFs) derived from rheumatoid arthritis (RA) patients. To optimize a potential therapeutic application we aimed at generating-fragments of Slit3 showing the same functional ability as the full-length molecule but having the advantage of a smaller size. Recombinant Slit3 proteins were expressed and analyzed by western blotting. Their activity was defined by functional assays such as migration assays with RASF and melanoma cells. Recombinant Slit3 containing only leucine rich repeat domain 2 (D2), the domain important for Robo binding and the minimal functional unit D2 dNC were both able to inhibit migration of RASFs as effectively as Slit3 with all 4 repeats. Collectively, our data showed that the ability of Slit3 to reduce the migratory activity of synovial cells from patients with RA and melanoma cells can be mimicked by small protein fragments derived from Slit3. Slit3 fragments may be helpful in therapeutic attempts; however, further studies are necessary in order to elucidate their activity in vivo.
CRIS-Team Scopus Importer:2022-08-05
Keywords: Melanoma; Migration; Proliferation; Recombinant proteins; Repellent factor; Rheumatoid arthritis; Roundabout; Slit